2005
DOI: 10.1182/blood-2004-04-1652
|View full text |Cite
|
Sign up to set email alerts
|

Risk of head and neck squamous cell cancer and death in patients with Fanconi anemia who did and did not receive transplants

Abstract: Hematopoietic stem cell transplant (SCT)is currently the only therapy that can restore normal hematopoiesis in patients with Fanconi anemia (FA). Patients with FA have a high baseline risk of squamous cell cancers (SCCs) of the head, neck, and esophagus, and SCT conditioning may increase SCC incidence. We evaluated the risks of SCC and death in 145 patients with FA in the North American Survey (NAS) cohort who did not receive transplants, and 117 patients with FA in the Hô pital Saint Louis (SLH) cohort who di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
248
0
13

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(266 citation statements)
references
References 48 publications
5
248
0
13
Order By: Relevance
“…76 In another study of 262 patients with FA, the 117 HCT recipients had a four-fold increased risk of developing SCC. 143 …”
Section: Non-transplant-related Risk Factorsmentioning
confidence: 99%
“…76 In another study of 262 patients with FA, the 117 HCT recipients had a four-fold increased risk of developing SCC. 143 …”
Section: Non-transplant-related Risk Factorsmentioning
confidence: 99%
“…Approximately 40% of FA patients develop a malignancy within 15-20 years after HSCT, 19 but indeed head and neck squamous cell carcinomas may occur earlier after transplant at a median of 8.2 years from the graft in patients conditioned with lowdose CY þ TAI who had extensive GvHD. 15 Another recent study 16 demonstrated that transplanted FA patients have increased risk and earlier occurrence of head and neck squamous cell carcinomas compared with non-transplanted FA patients and confirmed the strong association between GvHD and late malignancies. Although transplant results have now importantly improved in terms of quality and duration of engraftment and reduction of toxicity, it looks clear, on the basis of these data, that strategies in FA patients should now aim to minimize GvHD in the view of reducing the risk of late post transplant malignancies.…”
Section: Tablementioning
confidence: 98%
“…11 Of note is that GvHD, in addition to negatively impacting on survival and quality of life, is one of the major risk factors for the development of late tumours. 15,16 Over the recent years, fludarabine (Flu)-containing reduced-intensity conditioning regimens have become more popular and are being successfully employed also in FA. In a recently published cohort of 11 patients, 14 actuarial overall survival was 82%, TRM was 9%, GvHD was negligible and toxicity, on the whole, low.…”
Section: Current Options For Treatment Of Marrow Failurementioning
confidence: 99%
“…Humoral immunity was impaired in five of six patients. Four of the patients developed lymphoid malignancy at a median age of 12 years (range [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. One patient experienced a second, different lymphoid malignancy 8 years after chemotherapy for his first malignancy.…”
Section: Patient Characteristicsmentioning
confidence: 99%